Pengaruh Bekerja dari Rumah dan Kemampuan Kerja Terhadap Kinerja Pegawai Balai Bahasa Dimasa Pandemi Covid-19 - Sukamto Sukamto; Muji Gunarto (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This research was conducted to determine and analyze the effect of working from home and workability on employees' performance during the Covid-19 Pandemic at the South Sumatra Language Center. The results of preliminary studies show that work performance during the Covid-19 pandemic has decreased. The factors causing the observed decline in performance are thought to be due to the work from home system policy that is not used to be applied. The workability of employees is not sufficient, especially employees who are not familiar with information technology. During the work-from-home system activities, every employee is required to be able to work with information technology devices as a means of achieving performance targets. This type of research is conducted with a quantitative approach. Data collection techniques were obtained by distributing questionnaires to 36 employees as respondents who were sampled. Data analysis was performed using descriptive quantitative analysis and supported by qualitative analysis. Quantitative analysis used multiple regression analysis models. The results showed that partially working from home had a positive effect on the performance of the South Sumatra Language Center's employees. Workability significantly affects the performance of the employees of the South Sumatra Language Center. Simultaneously it also shows a significant influence, but workability has a more dominant influence than working from home.